Modelling of a PV system: a case study Kosovo - Blerina Bylykbashi; Risto V. Filkoski (Institute of Advanced Engineering and Science, 2023)
The modeling of a photovoltaic (PV) system used for the needs of the industrial sector is presented in this paper. Its analysis was done analytically using real one-year measurements during the system monitoring period and software-wise using premium PV*SOL software. System generated energy, maximum power point (MPP) voltage, final yield and average generated power are included in the analysis. The highest summer energy produced for real conditions is in July with 2811.86 kWh, the highest MPP voltage also presented in July with a value of 400 V. The final yield with a value of 103.07 kWh/kWp and the highest average power 16.6 kW as well. during the month of July. Where it can be seen that due to the Mediterranean atmospheric conditions in the place of application of the PV system, during the summer months the parameters are higher than during the winter months.